MPPT Full Bridge Converter using Fuzzy Type-2 - Annas Budi Prastyawan; Mohammad Zaenal Efendi; Farid Dwi Murdianto (Department of Electrical Engineering ITS and FORTEI, 2021)
Renewable energy application using Photovoltaic (PV) is developed as a conversion from solar energy into electrical energy. PV produces output power according to irradiation and temperature conditions. PV has a Maximum Power Point or MPP based on P-V characteristic curve. In certain conditions, PV has an unstable output power then the accuracy of the power generated is not maximum. MPPT method with conventional control is not optimal to resolves power inaccuracies in the system. When the system has a circuit problem, the conventional power converter will be damage. To achieve accuracy and maximize PV output, the Maximum Power Point method will find MPP. Using MPPT Fuzzy Type-2 method on the converter can reliably overcome the inaccuracies and tracking speed of PV power. Full Bridge Converter topology is used as a safety circuit with a high-frequency isolation transformer. Implemented on MATLAB/Simulink software, Simulation results in Model 1 show that the average power accuracy with Fuzzy Type-2 is 91.40% compared to Fuzzy Type-1 with an average power accuracy of 80.64%. In Model 2, Fuzzy Type-2 is 87.63% compared to Fuzzy Type-1 of 77.93%. MPPT method using fuzzy type-2 is better than using fuzzy type-1 in terms of power accuracy.Keywords: full bridge converter, fuzzy type-2, MATLAB/Simulink, maximum power point tracking, photovoltaic.